2018
DOI: 10.4049/jimmunol.1800620
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Lectin Receptor CD23 Is Required for Host Defense against Candida albicans and Aspergillus fumigatus Infection

Abstract: Infection by invasive fungi, such as ,, and , is one of the leading death causes for the increasing population of immunocompromised and immunodeficient patients. Several C-type lectin receptors (CLRs), including Dectin-1, -2, and -3 and Mincle can recognize fungal surface components and initiate the host antifungal immune responses. Nevertheless, it remains to be determined whether other CLRs are involved in antifungal immunity. Our recent study suggests that CD23 (CLEC4J), a CLR and also a well-known B cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 81 publications
1
23
0
Order By: Relevance
“…These glycosides decorate the cell wall proteins of the outer cell walls and the integral proteins in the cell membrane and may account for more than 80% of the mass of the glycoprotein [18,43,44]. A wide range of mannan-recognising immune receptors are present in myeloid and epithelial cells including the mannose receptor (MR), dectin-2, dectin-3, mincle, DC-SIGN, galectin-3, FcγR, CD14, CD23, TLR2, TLR4 and TLR6 [13,34,37,[45][46][47][48][49][50][51][52][53][54]. The number and diversity of mannan-recognising PRRs underlines their importance in primary immune recognition events.…”
Section: Introductionmentioning
confidence: 99%
“…These glycosides decorate the cell wall proteins of the outer cell walls and the integral proteins in the cell membrane and may account for more than 80% of the mass of the glycoprotein [18,43,44]. A wide range of mannan-recognising immune receptors are present in myeloid and epithelial cells including the mannose receptor (MR), dectin-2, dectin-3, mincle, DC-SIGN, galectin-3, FcγR, CD14, CD23, TLR2, TLR4 and TLR6 [13,34,37,[45][46][47][48][49][50][51][52][53][54]. The number and diversity of mannan-recognising PRRs underlines their importance in primary immune recognition events.…”
Section: Introductionmentioning
confidence: 99%
“…These glycosides decorate the cell wall proteins of the outer cell walls and the integral proteins in the cell membrane and may account for more than 80% of the mass of the glycoprotein [18, 43, 44]. A wide range of mannan-recognising immune receptors are present in myeloid and epithelial cells including the mannose receptor (MR), dectin-2, dectin-3, mincle, DC-SIGN, galectin-3, FcγR, CD14, CD23, TLR2, TLR4 and TLR6 [13, 34, 37, 4554]. The number and diversity of mannan-recognising PRRs underlines their importance in primary immune recognition events.…”
Section: Introductionmentioning
confidence: 99%
“…We present the landscape of transcriptomic changes between the two species and suggest aspects of differential immune system that might be associated with differential pathological characteristics. Several sets of E/S proteins that function at the host-parasite interface showed differential expression between the two species (for example, C-type lectins, RNF128, and other parasitic genes like PPT), which may probably be associated with the establishment of enhanced parasite invasion and motility in T. pseudospiralis (Hashimoto et al 2010; Child et al 2013; Guo et al 2018). Our analysis demonstrated that T. pseudospiralis showed enhanced ability of immune evasion through higher expression of secreted C-type lectins and PPT.…”
Section: Discussionmentioning
confidence: 99%